Letter from Carl D. Duncan to Patricia Whiting, July 27, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan writes a toast to Whiting, recounts an evening spent at a concert and mentions his progress on his plan to turn the deed of his house over to her.